Economywide Implications from US Bioenergy Expansion - Gehlhar, Mark; Somwaru, Agapi; Dixon, Peter B; Rimmer, Maureen T; Winston, Ashley R (American Economic Review, 2010)
Economywide Implications from US Bioenergy Expansion by Mark Gehlhar, Agapi Somwaru, Peter B. Dixon, Maureen T. Rimmer and Ashley R. Winston. Published in volume 100, issue 2, pages 172-77 of American Economic Review, May 2010